Evidences of Thermal and Non-Thermal Mechanisms coexisting in a Dense Plasma Focus D-D nuclear reactions - Castillo, F. (2000)
Dense plasma foci are the most efficient devices in the production of fast neutrons proceeding from deuterium nuclear fusion reactions. This work deals with experiments in a small plasma focus machine and attempts to distinguish neutrons of thermal origin from non-thermal neutrons, and the search for possible sources of both. Soft x-rays emitted by bremsstrahlung in a plasma focus were experimentally studied, using a multiple pin-hole camera with different aluminum absorbers in each hole. This method allows one to obtain the time-integrated soft x-ray image, as well as an estimation of the mean electronic temperature. The time-resolved soft x-ray intensity is registered with a filtered p-intrinsic-n (PIN) diode detector, shielded with a beryllium sheet. The time-resolved hard x-ray intensity (associated with particle acceleration) was registered using a plastic scintillator coupled to a fast photomultiplier tube. With a similar system, the time-resolved neutron emission is also registered. From the soft x-ray photographic studies, bright points with temperatures two or three times higher than the bulk plasma temperature are observed. These bright points (one or two per focus) can reach temperatures of over 7 keV, and their formation seems to correlate with successive necking produced by m = 0 instabilities in the pinch column. Time-integrated and time-resolved measurements of neutron yield, performed in comparison with time-resolved measurements of soft and hard x-ray radiation, show the different influence of thermal and non-thermal mechanisms in the nuclear fusion reactions.